Network Relations between Competitors (Example of Radio Advertizing in Moscow) - Анастасия Варзакова (Journal of Economic Sociology, 2010)
The author addresses the problem of the existence of contradictory relations between the same participants of the market at the same time: competition and collaboration. The object of the survey is market of the radio advertizing in Moscow, the market the main good of which is the commercial information. The subject of the study is the network relations between the participants of the radio advertizing market in Moscow and between the competitors. The survey is built on the expert and public interviews of the advertizing agents.